The Founding Myth of Rome: The Group of Aeneas in the Prado Museum and its Survival in Painting - Fernández Uriel, Pilar (Eikón / Imago, 2016)
Brief tour on the iconographic treatment of the called Group of Eneas, from its possible Greek and Etruscan origins to our days, with a special attention to its evolution in Rome and the pictorial creation of the seventeenth century deposited in the Prado National Museum, painted by Juan de la Corte, Francisco Collantes and Luca Giordano.